Teachers' knowledge levels about virtual information security - Karabatak, Songül; Karabatak, Murat (My University, 2018)
In this study, it was aimed to determine the level of knowledge about the threats of teachers' virtual information security and the precautions to be taken against these elements. The sample of the study carried out in the survey model was composed of 135 teachers who were selected by the method of unstructured element sampling among the teachers working in the high school in Elaz province center. The Information Security Achievement Scale was used as a data collection tool. Mean, percentage and frequency techniques and t test were used to analyze the data. It has emerged that most teachers in the study are not aware of the threats to the information in the virtual environment and do not know the precautions to be taken against to the attacks or threats to information security. Teachers' knowledge levels regarding threats and precautions related to information security differed significantly according to gender variables. At the end of the study, some suggestions were made about the security of virtual information.
Bildiri - Yayımlanmış
Keywords: Virtual information; Information security; Information security threats; Information security measures